Allowances for Corporate Equity in Practice - Klemm, Alexander (IMF Working Papers; Working Paper ;, 2006)
This paper provides an overview of full and partial allowance for corporate equity (ACE) tax systems in practice. In the recent past, ACE systems have been used in Austria, Croatia, and Italy. Brazil still applies a variant of such a system and Belgium introduced one this year. This paper summarizes the empirical literature on past ACE systems, and provides a theoretical and empirical assessment of the Brazilian ACE variant. The main finding is that the Brazilian reform introduced an ACE system for a minority of firms only, with the majority instead having a system of dividend deductibility. Despite the reduction in the tax preference for debt finance, capital structures have not changed much, but dividends have increased. Investment appears to have benefited from the reform, although the extent to which this was due to the new structure rather than the tax cut is unclear.